Academic stronghold of the period of new realities: attempts at analysis - Astakhova, E. (New Collegium, 2020)
The article describes certain aspects of the functioning of the academic staff of the modern university. Attention is focused on the fact that under the dramatic changes that have reshaped the world and tend to constantly gain momentum, the University needs to build new management models and fundamentally different mechanisms of interaction with the lecturer as the key player in the university world. The transition to the digital era and the total massovization of higher education coupled with a decrease in its quality are shaping a new reality of the university world to be lived in with new growth vectors to be defines.